TECHNOLOGY TRANSFER FROM THE UFMG TO A PRIVATE COMPANY: PROCESS AND RESULTS - Maria do Rosário Alves De Oliveira (International Journal of Innovation, 2016)
Economic growth and technological development are closely related. In this article, the process of technology transfer developed by the UFMG (a new sole cushioning system for a footwear industry in Nova Serrana city, in Minas Gerais State) is analyzed, using a case study. The data were collected from UFMG document research and through semi-structured interviews with the principal stakeholders. The process of technology transfer from the university to Crômic was a great learning process for both institutions. It led to a better relationship between the UFMG and the productive sector, opening up opportunities for new agreements and products. The study identified some aspects that need to be improved, such as simplification of procedures, bureaucracy reduction and regulation of the Brazilian Innovation Law within the departments of the university. The case study shows how much better cooperation between university and industry can contribute to the innovation process and improve competitiveness and the development of our country in these times of economic crisis.